Пошаговое объяснение:
[tex]1. \: \: 1) - 2 + 7 = 5[/tex]
[tex]2)3 + ( - 8) = - 5[/tex]
[tex]3) - \frac{2}{9} + \frac{5}{6} = - \frac{4}{18} + \frac{15}{18} = \frac{11}{18} [/tex]
[tex]4) - 3.9 - 8.4 = - 12.3[/tex]
[tex]5)4.5 - 8.3 = - 3.8[/tex]
[tex]6) - 1 \frac{3}{4} - 2 \frac{1}{12} = - 1 \frac{9}{12} - 2 \frac{1}{12} = - 3 \frac{5}{6} [/tex]
[tex]2. \: \: 1)6 + ( - 7) - ( - 15) - ( - 6) - 30 = - 1 - ( - 15) - ( - 6) - 30 = 14 - ( - 6) - 30 = 20 - 30 = - 10[/tex]
[tex]2)3 \frac{1}{6} + ( - 2 \frac{5}{9} ) - ( - 1 \frac{7}{12} ) = 3 \frac{3}{18} + ( - 2 \frac{10}{18} ) - ( - 1 \frac{7}{12} ) = \frac{11}{18} - ( - 1 \frac{7}{12} ) = \frac{22}{36} - ( - 1 \frac{21}{36} ) = 2 \frac{7}{36} [/tex]
[tex]3. \: \: 1)28 + x = 15 \\ x = 15 - 28 \\ x = - 13[/tex]
[tex]2)30 - x = - 17 \\ x = 30 - ( - 17) \\ x = 47[/tex]
[tex]3)x + 3.12 = - 5.43 \\ x = - 5.43 - 3.12 \\ x = - 8.55[/tex]
[tex]4)y - 3 \frac{5}{12} = - 2 \frac{7}{15} \\ y = - 2 \frac{7}{15} + 3 \frac{5}{12} \\ y = - 2 \frac{28}{60} + 3 \frac{25}{60} \\ y = \frac{19}{20} \\ y = \frac{95}{100} \\ y = 0.95[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
[tex]1. \: \: 1) - 2 + 7 = 5[/tex]
[tex]2)3 + ( - 8) = - 5[/tex]
[tex]3) - \frac{2}{9} + \frac{5}{6} = - \frac{4}{18} + \frac{15}{18} = \frac{11}{18} [/tex]
[tex]4) - 3.9 - 8.4 = - 12.3[/tex]
[tex]5)4.5 - 8.3 = - 3.8[/tex]
[tex]6) - 1 \frac{3}{4} - 2 \frac{1}{12} = - 1 \frac{9}{12} - 2 \frac{1}{12} = - 3 \frac{5}{6} [/tex]
[tex]2. \: \: 1)6 + ( - 7) - ( - 15) - ( - 6) - 30 = - 1 - ( - 15) - ( - 6) - 30 = 14 - ( - 6) - 30 = 20 - 30 = - 10[/tex]
[tex]2)3 \frac{1}{6} + ( - 2 \frac{5}{9} ) - ( - 1 \frac{7}{12} ) = 3 \frac{3}{18} + ( - 2 \frac{10}{18} ) - ( - 1 \frac{7}{12} ) = \frac{11}{18} - ( - 1 \frac{7}{12} ) = \frac{22}{36} - ( - 1 \frac{21}{36} ) = 2 \frac{7}{36} [/tex]
[tex]3. \: \: 1)28 + x = 15 \\ x = 15 - 28 \\ x = - 13[/tex]
[tex]2)30 - x = - 17 \\ x = 30 - ( - 17) \\ x = 47[/tex]
[tex]3)x + 3.12 = - 5.43 \\ x = - 5.43 - 3.12 \\ x = - 8.55[/tex]
[tex]4)y - 3 \frac{5}{12} = - 2 \frac{7}{15} \\ y = - 2 \frac{7}{15} + 3 \frac{5}{12} \\ y = - 2 \frac{28}{60} + 3 \frac{25}{60} \\ y = \frac{19}{20} \\ y = \frac{95}{100} \\ y = 0.95[/tex]